Evaluation Of Uterine Blood Flow In Threaten Abortion Using Color Doppler - Mohamed, Muna Ahamed; Gar-elnabi, MEM; Alseed, Mutasim Ahmed; Abdulla, Elsafi Ahmed; Hassan, Ikhlas Abdelaziz; Ibraheem, Asma; Dahy, Fatima (Asian Journal of Medical Radiological Research, 2013)
Threaten abortion is one of the most controversial condition concerning the judgment where subjectivity mostly cause a hesitant in conclusion, therefore the main objective of this study was to used color Doppler indices to identify threaten abortion case objectively. This study was conducted using GE Medical Systems LOGIC TM5 ultrasound machine. The data was collected form 200 pregnant ladies (100 with threaten abortion and 100 with normal pregnancies). The data were acquired using color Doppler where blood flow indices were recorded as well as the status of hematoma and pregnancy loss. The result of the study showed that there is a significant difference between the peak systolic velocity concerning the control group and threaten abortion at p = 0.05 as well the presence of hematoma or the occurrences of loss significantly alter the blood flow in threaten abortion group.